Atmospheric cold plasma induced nutritional & anti-nutritional, molecular modifications and in-vitro protein digestibility of guar seed (Cyamopsis tetragonoloba L.) flour. (June 2023) - Kheto, Ankan; Mallik, Akarshan; Sehrawat, Rachna; Gul, Khalid; Routray, Winny
Graphical abstract: Highlights: CPT significantly reduced the antinutritional factors while maintaining the nutritional value (10 kV-15 min). Increase in treatment duration degrade the carbohydrate, and protein content as well as crystallinity. High intensity cold plasma treatment (20 kV-20 min) was more effective to reduce the trypsin inhibition activity. In-vitro protein digestibility was significantly influenced by applied voltage. Cold plasma treatment (10 kV for 15 & 20 min) significantly (p < 0.05) improved the functional properties of guar seed flour. Abstract: The present study was carried out to investigate the effect of atmospheric cold plasma treatment on the nutritional, anti-nutritional, functional, morphological, and digestibility of guar seed ( Cyamopsis tetragonoloba L.) flour. Here, guar seed flour was kept inside the plasma reactor for 5 to 20 min at different power levels (10 & 20 kV). The cold plasma treatment (CPT) significantly (p < 0.05) reduced the carbohydrate (46.87 – 36.81 %), protein (27.15 – 25.88 %), and increased the WAC (1.89 – 2.91 g/g), OAC (1.18 – 2.17 g/g), FC (113 – 186.17 %), and pasting properties of guar seed flour. High-intensity plasma-treated samples (20 kV-20 min) contained lesser tannin, phytic acid, and saponin with reduced the nutritional value. The FTIR spectrum suggested that functional group formation or destruction might have occurred in the plasma-treated samples. Additionally, the crystallinity is reduced with increasing applied voltage or duration. The SEM analysis reveals that CPT resulted in the formation of rough surfaces with highly porous structures. On the other hand, CPT significantly reduced the trypsin inhibitor activity and had a minor impact on in-vitro protein digestibility except for the 20 kV-20 min treated sample. In PCA analysis, 10 kV-15 min treated samples exhibited better nutritional value, functional, and pasting properties with maximum impact of anti-nutritional factors. From the results, it can be concluded that treatment duration rather than the applied voltage plays a significant role in preserving the nutritional content.